Casino establishment, effects on income and unemployment : evidence from New York State - Wolny, Robert (University of Wisconsin--Whitewater, 2018)
Using New York State Public Use Microdata Areas (PUMAs) data from 2005 through 2011, I estimate the effects of casino establishment, and having casinos in surrounding PUMAs on per capita income and percentage unemployed. The main specification uses fixed effects to control for area specific time invariant unobserved heterogeneity. The primary result indicates that once unobserved time invariant heterogeneity is controlled for, there is no evidence that casino establishment, or of having casinos in the surrounding area has an effect on per capita income or percentage unemployed.
This file was last viewed in Microsoft Edge.
Keywords: Casinos--Location--New York (State); Casinos--Economic aspects--New York (State)